The risk of oral squamous cell carcinoma in patients with and without somatoform disorders including bruxism: A retrospective evaluation of 309,278 individuals - Heym, Marlene; Heiland, Max; Preissner, Robert; Huebel, Christopher; Nahles, Susanne; Schmidt-Westhausen, Andrea Maria; Preissner, Saskia; Hertel, Moritz (Frontiers in Oncology, 2023)
Background The question arises if there is an association of psycho-emotional stress and chronic soft tissue injuries caused by bruxism somatoform disorders with oral squamous cell carcinoma (OSCC). Methods Patients with and without “somatoform disorders including psychogenic disturbances” (International Classification of Diseases [ICD]-10 code F45.8), and/or “unspecific behavioral syndromes” (F59), and/or “sleep related bruxism” (G47.63), and/or “other sleep disorders” (G47.8) were retrieved from the TriNetX network to gain cohort I. Cohort II was formed by patients without the aforementioned diagnoses, and by matching for age, gender, tobacco use, and alcohol abuse. After defining the primary outcome as “OSCC” (ICD-10 codes C00−C14), a Kaplan-Meier analysis was performed, and risk ratio (RR) and odds ratio (OR) were calculated. Results After matching, each cohort accounted for 154,639 patients (59.7% females; 40.3% males; mean current age ( standard deviation) = 43.4  24.5 years). Among cohorts I and II, 907 and 763 patients, respectively, were diagnosed with OSCC within 5 years (risk of OSCC = 0.6% and 0.5%), whereby the risk difference was significant (p  0.001; Log-Rank test). RR and OR were 1.19 (95% confidence interval (CI), lower = 1.08 and upper = 1.31) and 1.19 (95% CI, 1.08−1.31). Conclusions Psycho-emotional stress and/or chronic mucosal injuries may play a role in carcinogenesis. However, the results need to be interpreted cautiously due to limitations of the applied approach. It may thus far only be concluded that further research is necessary to investigate hypotheses regarding psychogenic carcinogenesis and tumor formation due to chronic tissue trauma.